WŁADZA TRZECIA „NEUTRALNA” - Sylwestrzak, Andrzej (Zeszyty Prawnicze, 2016)
THIRD POWER: NEUTRAL ONE Summary The issues discussed in the article cover six areas: a/ law-based state and the division of power, b/ division of power in the doctrine, c/ division of power in Polish constitutionalism, d/ normative classification of constitutional authority, e/ the political power, opposition power and neutral power, f/ concluding remarks. The aim of the article is to present the arguments for “neutral power” as the creative factor indispensable in the proper functioning of the law-based state. Within Montesquieu tripartite classification, “neutral power” entailes the nessesity to restracture juridical power so thet it will include financial control, constitutional bank control as well as ombudsmen. Accepting the division into ruling power and opposition power, “neutral power” (including the judiciary and the ombudsmen) indicates the kind of power Montesquieu advocated, trough in its more prominent role of the mediator between the powers. “Neutral power”, described in these terms, ought to be independent of the remaining powers through the system of internal elections to all the posts, performer by the Supreme Court representatives. Judges of the Constitutional Tribunal, the Ombudsman or the Cheef of Governmenmt Inspectorate ought to be elected by the Supreme Court Judges.